Neurological manifestations in scrub typhus from a case series in Southern India - Vasantha Kamath; Shreyashi Ganguly; B Himabindu (Wolters Kluwer Medknow Publications, 2021)
Scrub typhus is an acute febrile illness caused by Orientia tsutsugamashi. CNS is the most crucial target in other rickettsial diseases and historically, the neurological disease burden was considered low in scrub typhus. However, there is growing evidence in literature that O. tsutsugamushi does invade the CSF and CNS invasion may be seen in 2-5 % cases of tsutsugamushi disease. O. tsutsugamushi parasitises endothelial cells both in the periphery as well as in the brain. The disease is characterized by focal or disseminated vasculitis and perivasculitis. Scrub typhus has protean manifestations. CNS involvement is rare but it should be considered as an important differential in the setting of known areas of scrub typhus outbreak. Meningoencephalitis with or without focal neurological deficits is the commonest clinical picture. However, the neurological manifestations can be highly variable. In our case series out of 81 patients who were diagnosed with scrub typhus, only 5 patients had neurological manifestations. All patients presented with altered sensorium. GCS was decreased in all patients. It was <10 in 60% cases. Neck rigidity and signs of meningeal irritation was present in 80% cases. There was no sign of papilloedema, cranial nerve involvement, focal neurological deficits. 2 of the patients had seizure which was GTCS in semiology. CSF in all cases showed lymphocytic predominance (between 150 and 400 cells/ mm3) with high protein and low to normal CSF sugar levels. NCCT brain was normal. MRI brain showed meningeal enhancement in 60% cases. Additionally, hyperintense signal on T2 was observed in 60% cases. Confirmation of the case requires serological evidence. CSF and neuroimaging picture are not pathognomonic. In the setting of acute fever, headache along with eschar or macular rash, scrub typhus must be ruled as a cause of neurological manifestations, such as altered sensorium, and seizure.